2022
DOI: 10.3390/diagnostics12020468
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Optical Coherence Tomography Angiography (OCT-A) in Neurological Diseases

Abstract: Optical coherence tomography angiography (OCT-A) was commercially introduced in 2014. OCT-A allows a fast, non-invasive, three-dimensional analysis of the retinal vasculature from the vitreoretinal interface to the choriocapillaris. The results can be evaluated separately in automated or custom-defined retinal layers. Since its introduction, OCT-A has also been used in patients with neurological diseases in order to find and characterize retinal biomarkers. Many neurological diseases have retinal manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…This point is directly related to the misdiagnosis of FH in the general population [ 4 ]. In addition to this, exclusion criteria were based only on the absence of ophthalmological disease, while other general affectations such as neurological disorders could also impact retinal vascular densities [ 40 ]. Concerning the volunteers constituting the CT group, they were recruited on the basis of a self-reported absence of personal or familial FH history and not being on cholesterol-lowering medications.…”
Section: Discussionmentioning
confidence: 99%
“…This point is directly related to the misdiagnosis of FH in the general population [ 4 ]. In addition to this, exclusion criteria were based only on the absence of ophthalmological disease, while other general affectations such as neurological disorders could also impact retinal vascular densities [ 40 ]. Concerning the volunteers constituting the CT group, they were recruited on the basis of a self-reported absence of personal or familial FH history and not being on cholesterol-lowering medications.…”
Section: Discussionmentioning
confidence: 99%
“…For the macula region, the OCTA scan generates projections of the macula's vascular network (i.e. the choriocapillaris and choroid vasculature) at preset depths, permitting the ophthalmologists to diagnose and follow up on different eye diseases in the macula region [11][12][13][14]40]. Therefore, the research in OCTA is evolving.…”
Section: Introductionmentioning
confidence: 99%
“…OCTA, an noninvasive and 3D angiography technique for retinal and choroidal vessels, has gained increasing importance as a fast and non-invasive method for analyzing fundus microvasculature in a wide variety of systemic diseases not only hypertension and diabetes but also neurological diseases 7 , autoimmune disease 8 , and cardiovascular systemic diseases (CVD) 9 . Currently, several studies revealed that carotid arterial disease (CAD) is an independent related factor of retinal microvascular disease assessed by OCTA in type 2 diabetes patients 10 .…”
Section: Introductionmentioning
confidence: 99%